Pneumonia treatment by photodynamic therapy with extracorporeal illumination - an experimental model - Geralde, Mariana C.; Leite, Ilaiali S.; Inada, Natalia M.; Salina, Ana Carolina G. [UNESP]; Medeiros, Alexandra I. [UNESP]; Kuebler, Wolfgang M.; Kurachi, Cristina; Bagnato, Vanderlei S. (Wiley-Blackwell, 2017)
Infectious pneumonia is a major cause of morbidity/mortality, mainly because of the increasing rate of microorganisms resistant to antibiotics. Photodynamic Therapy (PDT) is emerging as a promising approach, as effects are based on oxidative stress, preventing microorganism resistance. In two previous studies, the in vitro inactivation of Streptococcus pneumoniae using indocyanine green (ICG) and infrared light source was a success killing 5 log10 colony-forming units (CFU/mL) with only 10 lmol/L ICG. In this work, a proof-of-principle protocol was designed to treat lung infections by PDT using extracorporeal illumination with a 780 nm laser device and also ICG as photosensitizer. Hairless mice were infected with S. pneumoniae and PDT was performed two days after infection. For control groups, CFU recovery ranged between 10(3)-10(4) / mouse. For PDT group, however, no bacteria were recovered in 80% of the animals. Based on this result, animal survival was evaluated separately over 50 days. No deaths occurred in PDT group, whereas 60% of the control group died. Our results indicate that extracorporeal PDT has the potential for pneumonia treatment, and pulmonary decontamination with PDT may be used as a single therapy or as an antibiotics adjuvant.
Keywords: Extracorporeal illumination; indocyanine green; photodynamic therapy; pneumonia; Streptococcus pneumoniae